Gamifikasi dalam Pembelajaran Siswa Sekolah Dasar - Tellma Tiwa (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2020)
Abstract: Covid-19 pandemic change the old way of learning between teacher and students. Teachers need to make a change and innovation to finish all the material, make sure that all students get the knowledge, competent in every aspect, and also adapt the old form of curriculum with all the changes that happen. The methods that have been used so far, are not effective enough. Students which are the ‘gadget native” generation who are familiar with gadgets makes technology as the solution for teachers to optimize the learning process. Gamification is one of a tech-friendly method for students. It’s a win-win solution for both teacher and students. Keyword : Pendidikan anak, covid-19, gamifikasi Abstrak : Pandemi covid-19 mengubah metode belajar-mengajar antara guru dan siswa. Tuntutan pencapaian materi, kompetensi yang harus dikuasi, dan kurikulum yang tersedia membuat guru perlu melakukan inovasi. Metode yang selama ini digunakan dirasa kurang menjawab kebutuhan siswa. Siswa yang adalah generasi “gadget native” secara natural fasih menggunakan gawai. Teknologi menjadi solusi bagi guru untuk mengoptimalkan pembelajaran. Gamifikasi adalah salah satu solusi metode pembelajaran dengan teknologi ramah anak. Materi dan tuntutan kurikulum terpenuhi, siswa belajar dan menguasai materi dengan cara menyenangkan. Kata Kunci : Pendidikan anak, covid-19, gamifikasi